Resíduos do processamento do xerelete (caranx latus, agassiz, 1831) como fonte de proteases alcalinas - Sebastião, Jucelinelcia Housseina Seidi (2023)
Fishery waste industrially produced and improperly discarded is a source of pollution, and its reuse for the extraction of biological macromolecules for industrial applications has grown. The Horse-eye jack (Caranx latus) is a fish species with great commercial interest on the Brazilian coast. The reuse of waste generated in its processing to obtain proteases with industrial applications can help to reduce the enzymes deficit at industries. Through ammonium sulfate precipitation, an enzyme concentrate (F20-80%) with high trypsin activity was obtained from the horse-eye jack pyloric cecum crude extract. The effect of inhibitors and other chemical agents on F20-80% tryptic activity was evaluated. The physicochemical characteristics of the trypsins present in F20-80% were also determined. A maximum tryptic activity of F20-80% was observed at pH 10.5. The trypsins present in F20-80% were stable from pH 6 to pH 11.5. The optimum temperature for F20-80% tryptic activity was determined to be 45 °C and the thermal stability was in the range of 25 to 45 °C for 30 min. The metallic ions Al3+, Cu2+ e Hg2+ and the TLCK inhibitor promoted a high inhibition of the trypsin activity present in F20-80%. The chelating agent EDTA and the TPCK inhibitor promoted a slight inhibition of the F20-80% tryptic activity. F20-80% maintained 70% of its maximum activity in the presence of 7.5% (w/v) NaCl. The F20-80% was not compatible with the formulation of the commercial powdered detergents tested. The present study suggests that Caranx latus fish viscera may be promising sources of trypsin-like alkaline proteases. Despite its incompatibility with the chemical formulation of the tested detergents, the physicochemical characteristics presented by these enzymes, as well as their stability in the presence of high NaCl concentrations, indicate a promising use in other commercial sectors, such as collagen, gelatinthe and food industries. However, other studies are needed to better evaluate its applicability within the processes in each industry.